Growth and development of multiple waterhemp (Amaranthus tuberculatus) cohorts in corn and soybeans - Arsenijevic, Nikola; DeWerff, Ryan; Conley, Shawn; Ruark, Matthew Dwain; Werle, Rodrigo (Frontiers in Agronomy, 2022)
Waterhemp is a troublesome weed species in cropping systems throughout Wisconsin and much of the US Midwest. Coupled with extended emergence window, rapid growth, high genetic diversity, and herbicide resistance to multiple sites of action, waterhemp represents a major challenge for chemical-based weed control. The objective of this experiment was to evaluate the impact of soybean and corn canopy on growth and development of multiple waterhemp cohorts in 2019 and 2020. Treatments consisted of narrow- (38 cm row spacing) and wide-row (76 cm row spacing) soybeans, corn (76 cm row spacing), and fallow (no crop), with 6 waterhemp transplant timings (cohorts) in 2019 and 2020, respectively. Waterhemp seedlings grown in the greenhouse were transplanted at the 2-3 true leaves growth stage to the field at 10-day increments throughout the typical waterhemp emergence season for Wisconsin (June-July). Waterhemp plants were measured for height and harvested for biomass when they reached the flowering stage. The number of days from the first transplant timing to result in 50% and 90% biomass and height reduction (ED50 and ED90) of subsequent waterhemp cohorts were estimated and used as indicators of weed suppression ability by the respective crop. Narrow-row soybeans required fewer days to suppress 50% growth of new waterhemp cohorts followed by corn, wide row soybeans, and fallow, respectively (4, 6, 9, and 14 d for 50% biomass reduction, and 10, 14, 18, and 42 d for 50% height reduction, respectively). Similarly, narrow-row soybeans required fewer days to suppress 90% biomass of waterhemp, followed by corn, wide-row soybeans, and fallow (11, 15, 18, and 78 d, respectively). Conversely, narrow and wide-row soybeans required fewer days to suppress 90% height of new waterhemp cohorts followed by corn and fallow (20, 26, 43, and 85 d, respectively). Rapid soybean canopy closure (e.g., planting soybeans earlier and in narrow row-spacing) combined with other integrated weed management practices have the potential to reduce reliance on POST herbicide application and mitigate herbicide resistance evolution. In corn, mid- to late-season monitoring and management of later emerging waterhemp cohorts is recommended due to longer time required to reach 90% waterhemp growth suppression.